2017
DOI: 10.1002/pc.24561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treated coir fiber/coconut shell powder and aramid fiber on mechanical properties of vinyl ester

Abstract: The surfaces of coir fiber (CF) and coconut shell powder (CSP) were modified by alkali and silane treatment respectively to investigate the consequent effects on reinforcement of vinyl ester (VE) composites. Mono‐composites of VE with surface treated CFs and CSP as well as their hybrid composites with as‐received aramid fibers (AFs) have been prepared by hand layup followed by compression molding methods. The effectiveness of surface treated reinforcements in improving the mechanical properties of the composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Natural fibers are environmentally friendly materials and these have outstanding properties preferable to many man‐made fibers 4 . Natural fiber polymer composites contain polymer as matrix that entrenched through extraordinary property of the natural fibers, such as bagasse, banana ribbon, Indian mallow, kusha grass, red banana peduncle, nendran, vetiver, banana peduncle, jute, flax, oil palm, kenaf, sisal, Cissus quadrangularis , coir fiber/coconut shell powder and roselle fiber 5–16 …”
Section: Introductionmentioning
confidence: 99%
“…Natural fibers are environmentally friendly materials and these have outstanding properties preferable to many man‐made fibers 4 . Natural fiber polymer composites contain polymer as matrix that entrenched through extraordinary property of the natural fibers, such as bagasse, banana ribbon, Indian mallow, kusha grass, red banana peduncle, nendran, vetiver, banana peduncle, jute, flax, oil palm, kenaf, sisal, Cissus quadrangularis , coir fiber/coconut shell powder and roselle fiber 5–16 …”
Section: Introductionmentioning
confidence: 99%
“…The formation of silanol bonds and hydrogen bonds on fiber surfaces due to silane treatment enhances the adhesion between the filler-matrix, resulting in superior properties. Composites reinforced with treated fibers may be used in automobiles for structural applications [48]. Ultrahigh-molecular-weight polyethylene (UHMWPE) is combined with the polymeric filler polytetrafluoroethylene (PTFE) and AFs using the CM technique.…”
Section: Aramid Fiber and Its Hybrid Compositesmentioning
confidence: 99%
“…The addition of treated coir fiber/coconut shell powder and AFs improved the mechanical properties of the VE composites, with the highest mechanical properties achieved at a 10 wt.% fiber content. The study found that the addition of AFs had a more significant effect on the tensile and impact strength of the composites, while the addition of treated coir fiber/coconut shell powder had a more significant effect on the flexural strength [48]. Yahaya et al [17] investigated the ballistic impact properties of woven kenaf-aramid fiber hybrid composites.…”
Section: Synthetic Fiber-reinforced Polymer Compositesmentioning
confidence: 99%
“…The outcomes are accounted for in this paper. [18] In this way, it is extremely fascinating to concentrate on the impact of ball processing time combination. As referenced above, coconut shell powder has incredible potential for structure.…”
Section: Introductionmentioning
confidence: 99%